Essential oil composition and variability of Thymus lotocephalus and Thymus×mourae - Salgueiro, Lígia R. (2000)
The composition of the essential oils of four populations of Thymus lotocephalus G. López and R. Morales and one population of T.×mourae Paiva and Salgueiro, two endemic taxa from Portugal, was investigated mainly by GC and GC-MS. T×mourae is a natural hybrid between T. lotocephalus and T. mastichina (L.) L. subsp. donyanae R. Morales, which essential oil was analysed for the first time. In its oil, it was possible to find compounds of both parents, which could enable us to confirm its intermediate status between those two taxa. 1,8-Cineole and borneol were the main constituents in the essential oil of T.×mourae, whereas linalool, geranyl acetate and 1,8-cineol were the major ones in T. lotocephalus. Intermedeol was also an important constituent in the oils of both taxa. Nevertheless, the volatile oils of the four populations investigated of T. lotocephalus showed important differences among the main constituents. In order to study their infraspecific variability, the results obtained in the analysis of individual plants were submitted to a Principal Component and Chemometric Cluster Analyses. Five types of essential oils were found: linalool, 1,8-cineole, linalool/1,8-cineole, linalyl acetate/linalool and geranyl acetate.